2019
DOI: 10.1371/journal.pone.0224029
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding policy, practice and influences in South Africa, 1980 to 2018: A mixed-methods systematic review

Abstract: BackgroundIn 2011, South Africa committed to promoting exclusive breastfeeding (EBF) for six months for all mothers, regardless of HIV status, in line with World Health Organization recommendations. This was a marked shift from earlier policies, and with it, average EBF rates increased from less than 10% in 2011 to 32% by 2016.ObjectivesThe aim of this mixed-methods systematic review was to describe EBF practices in South Africa and their multi-level influences over four policy periods.MethodsWe applied PRISMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 94 publications
0
56
0
Order By: Relevance
“…An initial list of content areas and Fig. 1 Breastfeeding Conceptual Framework for South Africa [8] draft questions were prepared by the study designers who are mHealth and breastfeeding experts respectively. This list was then revised by the first author based on prior experience conducting interviews in South Africa.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…An initial list of content areas and Fig. 1 Breastfeeding Conceptual Framework for South Africa [8] draft questions were prepared by the study designers who are mHealth and breastfeeding experts respectively. This list was then revised by the first author based on prior experience conducting interviews in South Africa.…”
Section: Data Collectionmentioning
confidence: 99%
“…In order to identify appropriate interventions to promote breastfeeding, Rollins et al [7] have proposed that breastfeeding determinants should be analyzed using a socioecological framework. The framework was further adapted by Nieuwoudt and colleagues [8] to account for intention during the antenatal period, as well as South Africa-specific feeding guideline changes over time ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers may be aware of the significance of the information in booklets, but the booklets are written in languages (usually English or Afrikaans) that are unfamiliar to many caregivers. Some of the advice, such as best feeding practices (including exclusive breastfeeding for at least 6 months followed by the introduction of solid food with high iron content) is not possible given people's material circumstances and conditions of employment, for middle class as well as poor women (Ngcowa, 2019;Nieuwoudt et al, 2019). Le Roux et al (2017) found that despite carefully completed booklets, caregivers had to return to clinics repeatedly because of vaccine and medication stock-outs.…”
Section: Neonatal Cyborgsmentioning
confidence: 99%
“…The evidence indicates that the benefits of breastfeeding outweigh the risks of not breastfeeding, regardless of the maternal HIV status. 13 , 14 , 15 As the HIV epidemic matures, it is clear that the breastfeeding period must be one of the main priorities in the prevention of vertical transmission of HIV. New innovative strategies are required to achieve and maintain maternal viral suppression in the period after birth, whilst simultaneously promoting breastfeeding as a major child survival strategy.…”
Section: Introductionmentioning
confidence: 99%